Preparation and Chemical Composition of the Cell Membranes of Developmental Reticulate Forms of Meningopneumonitis Organisms - Tamura, Akira (1967)
The outer limiting membranes of developmental reticulate forms of the meningopneumonitis organism were purified by a combination of differential centrifugation, trypsin digestion, and sodium dodecyl sulfate treatment, and their physical and chemical properties were compared with those of outer envelopes of mature dense forms of this organism. Reticulate bodies were easily disrupted by short periods of sonic treatment and were lysed by trysin digestion, in contrast to the dense bodies which were resistant to these treatments. In electron micrographs, reticulate body membranes were seen as very thin, flattened structures, whereas dense-body envelopes showed folding rigid membranes. The results of chemical fractionation of (32)P-labeled purified preparations indicated that reticulate body membranes have smaller amounts of phospholipid, and are more dense than cell walls of the mature forms. The analysis of amino acid composition of reticulate body cell membranes showed that they do not contain cystine or methionine, both of which were found in cell walls of dense bodies. These results clearly show that there are significant differences in the chemical and physical properties of the outer envelopes of the developmental and mature forms of this organism.